RhoC and ROCKs regulate cancer cell interactions with endothelial cells. Issue 6 (22nd January 2015) - Reymond, Nicolas; Im, Jae Hong; Garg, Ritu; Cox, Susan; Soyer, Magali; Riou, Philippe; Colomba, Audrey; Muschel, Ruth J.; Ridley, Anne J.
Abstract : RhoC is a member of the Rho GTPase family that is implicated in cancer progression by stimulating cancer cell invasiveness. Here we report that RhoC regulates the interaction of cancer cells with vascular endothelial cells (ECs), a crucial step in the metastatic process. RhoC depletion by RNAi reduces PC3 prostate cancer cell adhesion to ECs, intercalation between ECs as well as transendothelial migration in vitro. Depletion of the kinases ROCK1 and ROCK2, two known RhoC downstream effectors, similarly decreases cancer interaction with ECs. RhoC also regulates the extension of protrusions made by cancer cells on vascular ECs in vivo. Transient RhoC depletion is sufficient to reduce both early PC3 cell retention in the lungs and experimental metastasis formation in vivo. Our results indicate RhoC plays a central role in cancer cell interaction with vascular ECs, which is a critical event for cancer progression. Highlights: RhoC acts in cancer cells to mediate their interaction with endothelial cells in vitro and in vivo. RhoC regulates cancer cell attachment to and insertion between endothelial cells prior to transendothelial migration. The RhoC effectors ROCK1 and ROCK2 act similarly to regulate cancer cell interaction with endothelial cells. Transient RhoC depletion is sufficient to reduce cancer cell survival in lung blood vessels and metastasis formation.